(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The questions of co-operation of artist and spectator, intercourse of those and other, through perception of artistic work are examined in the article. Reasons and methods of creation of artistic work are analyzed, and conformities to the law of his perception by a spectator.